2010
DOI: 10.1093/jnci/djq068
|View full text |Cite
|
Sign up to set email alerts
|

Race and Colorectal Cancer Disparities: Health-Care Utilization vs Different Cancer Susceptibilities

Abstract: We observed a lower follow-up for screen-detected abnormalities among blacks when compared with whites but little difference in the yield of colorectal neoplasia. Health-care utilization may be playing more of a role in colorectal cancer racial disparity than biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
157
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(167 citation statements)
references
References 32 publications
8
157
1
1
Order By: Relevance
“…Population differences have been observed in many human complex traits, including disease susceptibility, 29,30 drug sensitivity 31,32 and gene expression. [6][7][8] Genetic polymorphisms have undergone extensive evaluation for their potential role in these observed expression may contribute to observed population differences in mRNA expression levels and possibly other complex human traits.…”
Section: Discussionmentioning
confidence: 99%
“…Population differences have been observed in many human complex traits, including disease susceptibility, 29,30 drug sensitivity 31,32 and gene expression. [6][7][8] Genetic polymorphisms have undergone extensive evaluation for their potential role in these observed expression may contribute to observed population differences in mRNA expression levels and possibly other complex human traits.…”
Section: Discussionmentioning
confidence: 99%
“…Underutilization of screening in some racial/ethnic groups contributes to disparities in CRC death rates, [11][12][13][14][15][16] particularly for blacks, who have the highest CRC mortality rates in the US. 17,18 These screening disparities may be related to lack of awareness or acceptance, poor patient-physician communication, economic and structural barriers such as lack of health insurance coverage or usual place of medical care.…”
Section: Introductionmentioning
confidence: 99%
“…It is the only gastrointestinal cancer that has been shown to be amenable to screening in randomized control trials [14,15]. However, blacks are less likely to be screened [10,11] or to have optimal diagnostic follow-up after an abnormal screening [16]. Studies have also suggested that blacks tend to receive substandard cancer care when compared to whites [17] with reduction and elimination of black-white differences in survival when equitable treatment was received by patients regardless of race-ethnicities [18,19].…”
mentioning
confidence: 99%